1977
DOI: 10.1111/j.1365-2923.1977.tb00606.x
|View full text |Cite
|
Sign up to set email alerts
|

Teaching decision making to medical undergraduates by computer-assisted learning

Abstract: Undergraduate medical students improve their ability to make patient management decisions through using computer-assisted learning. With this problem-solving approach an improvement in their factural knowledge also occurs and they retain a significant amount of the content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1978
1978
1987
1987

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…However, an indication of the value of CAL was given by the marked decrease in the mean percentage of serious errors (20.7% to 10.3%) for students who repeated the first case attempted. In an assessment carried out by Murray et al (1977), it was found that this form of CAL improved significantly the student's factual knowledge and decision‐making ability.…”
Section: Discussionmentioning
confidence: 99%
“…However, an indication of the value of CAL was given by the marked decrease in the mean percentage of serious errors (20.7% to 10.3%) for students who repeated the first case attempted. In an assessment carried out by Murray et al (1977), it was found that this form of CAL improved significantly the student's factual knowledge and decision‐making ability.…”
Section: Discussionmentioning
confidence: 99%
“…A variant of this is the type of question in which instead of a simple ‘yes’ or ‘no’ decision, for each choice the respondent has to rate the course of action or statement on a one‐to‐five scale, one being something which should certainly not be done or something certainly wrong, two something that should probably not be done or is probably wrong, three an equivocal action or decision, four something that should probably be done or is probably correct and five something that should certainly be done or is certainly correct. This type of question has been used in both written PMPs (Harden et al , 1979) and computer‐based PMPs (Murray, Dunn et al , 1977; Murray, Cupples et al , 1977).…”
Section: Stages In a Pmpmentioning
confidence: 99%
“…The student then makes a final diagnosis. The patient's condition remains unchanged throughout the simulation (De Dombal, Hartley & Sleeman, 1969; Harless et al , 1971; Murray et al , 1977). However, in some models fixed changes in the patient's condition are presented to the student at predetermined intervals (Friedman, 1973, 1978).…”
Section: Introductionmentioning
confidence: 99%